Model Manajemen Modal Kerja Pada Koperasi Unit Desa Tani Wilis Tulungagung - Ahmad Aji Ubaidillah Kari; Achmad Murdiono (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2022)
Formulating a working capital management model at KUD Tani Wilis Tulungagung is the aim of this research. Researchers conducted interviews and observations to produce descriptive qualitative research. Descriptive research aims to describe the existing phenomena. Qualitative research is used to explore and interpret human and social issues. Source triangulation was used to check the validity of this study. The results of this study can be concluded that the working capital owned by KUD Tani Wilis in the form of cash, receivables, inventories, and prepaid transactions. The working capital management model at KUD Tani Wilis consists of the planning stage, the organizing stage, the implementation stage, and the evaluation stage. These stages are interconnected and one of them cannot be left out. KUD Tani Wilis has an awareness of the importance of working capital management and consistently carries out this management. With the working capital management model, KUD Tani Wilis can increase its profits from year to year.